Tissue Necrosis due to Chloroform: A Case Report - Mohammadzadeh Akhlaghi, Nahid; Mohajeri, Ladan Baradaran; Fazlyab, Mahta (Iranian Endodontic Journal, 2013)
For many years, gutta-percha has been the root canal filling material of choice. Chloroform is one of the most efficient solvents widely used for gutta-percha removal in retreatment cases, despite being toxic and carcinogenic. The present case report discusses a chloroform extrusion through an existing perforation to the surrounding periodontal ligament space and subsequent necrosis in supporting bone and tissues, during an endodontic retreatment visit for an addicted patient. Subsequently, the management and preventive options are reviewed.